Are you experienced [compact disc] - Hendrix, Jimi (Sony Music, 2010)
Are You Experienced is the debut album by English/American rock band The Jimi Hendrix Experience. Released in 1967, it was the first LP for Track Records. The album highlighted Jimi Hendrix's R & B-based, psychedelic, distortion-and feedback-laden electric guitar playing and launched him as a major new international star.